Effect of temperature on oxidation behavior and occurrence state of sulfur in KR slag - Li, Jianli; Jiang, JiaJun; Xiao, Chao; Yu, Yue (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
The main component (CaO) in KR (Kambara reaction) desulfurization slag is a high value slag raw material for converter smelting, and attempts to utilize KR desulfurization slag in converter smelting are conducive to reducing the buildup of KR desulfurization slag and improving the economic efficiency of converter smelting. However, the removal of sulfur in the slag is a key issue. The influence of temperature on the sulfur oxidation behavior in KR slag in the form of synthetic slag was investigated. SEM-EDS, XRD, and an infrared carbon and sulfur analyzer were used to analyze and detect the oxidized slag samples at different temperatures. The results show that the desulfurization rate increases gradually with the increase in temperature at a flow rate of Ar-50%O2 of 2 L/ min. Under the condition of low temperature (T ≤ 1220 oC), the desulfurization rate of slag is less affected by temperature. When T > is 1220 oC, the desulfurization rate of slag is greatly affected by temperature. When the reaction temperature reaches 1420 oC, the desulfurization rate reaches 93.5%. Furthermore, the types of sulfur-containing phases in the oxidized slag samples gradually decrease with the increase of temperature, and the sulfur in the oxidized slag samples is mainly present in the silicate phase when the temperature is less than or equal to 1220 oC.